'Be water' strategy of liquid lithium sulfide enables 0.2 V potential barrier for high-performance lithium–sulfur batteries. (September 2021) - Zhao, Y.; Zhang, Z.; Wu, R.; Lyu, C.; Zhao, X.; Xu, H.; Xiang, J.; Zha, C.; Ouyang, G.; Wang, L.
Abstract: The Li2 S-based lithium–sulfur battery is an attractive option for next-generation energy storage, which can couple with Li-free anodes to reveal a feasible approach to circumvent the safety issue of the highly reactive lithium metal. However, bulk Li2 S needs a high activation potential with the electrolyte decomposition in the initial oxidation and shows uncontrollable polysulfides migration in the cycling. To address these challenges, a facile solvation strategy to fully dissolve bulk Li2 S is developed to achieve the only 0.2 V potential barrier without any hyperthermal treatments and/or additives. Meanwhile, the novel VB2 materials offer abundant active sites to confine polysulfide migration with the low self-lithiation property. With those ingenious tailoring of cell designs, the VB2 -based liquid Li2 S cell achieves a stable capacity (530 mAh/g with 2 mg/cm 2 ) at 1.0 C with an extremely low fading capacity (78% capacity retention) after 500 cycles. More importantly, this strategy provides a novel insight into the liquid Li2 S-based lithium–sulfur battery with a better performance for the commercial applications. Graphical abstract: Image 1 Highlights: A facile solvation strategy of bulk Li2 S. The high-performance of VB2 materials. The better performances of lithium-sulfur batteries.